MadGraph Implementations of the Chirality-Flow Formalism for QED - Boman,Emil (2023)
The chirality-flow formalism has been proven to simplify the calculation of helicity amplitudes, both analytically and in a first numerical implementation developed as an extension of MadGraph5_aMC@NLO. Expanding on this work, two new implementations have been developed. The first provides an alternative algorithm for the evaluation of diagrams, where helicity amplitudes are obtained by combining pre-calculated spinor inner products, rather than recalculating inner products for every vertex where they are needed. Even though this new algorithm is more effective than MadGraph5_aMC@NLO, it is not an improvement over its predecessor, though some cases where recycling could be used for optimizations have been identified. The second implementation is an extension into massive QED, which shows that the chirality-flow formalism has better performance than MadGraph5_aMC@NLO within this sector of the Standard Model as well. Even though this gain is not as high as in the massless sector, it is still higher than expected.